"Woman as Creator": Margarete Schütte-Lihotzky's and Juliette Tréant-Mathé's Design of the New Dwelling in Interwar Europe. Issue 2 (4th May 2022) - Ford, Caroline
Abstract: This article explores the trajectories of two women architects, Margarete Schütte-Lihotzky and Juliette Tréant-Mathé, who, in contrast to most of their female counterparts in interwar Europe, devoted much of their architectural work to the design of social housing. It examines the nature of the shared social activism that informed their work, while considering the gendered dimension of their architectural designs in the 1920s and 1930s. It assesses how Schütte-Lihotzky, in particular, participated in the discussions about the relationship between Existenzminimum, or the minimum level of conditions needed for living, and the construction of housing for single professional women, and how the design of domestic architecture could respond to their needs. Finally, it examines their largely unexplored contributions as women architects to broader debates about "the new dwelling" and the role of architecture in modern life more generally.